Volatility accounting: A production perspective on increased economic stability - Kevin J. Stiroh (Federal Reserve Bank of New York, 2006)
This paper examines the declining volatility of U.S. output growth from a production perspective. At the aggregate level, increased output stability reflects decreased volatility in both labor productivity growth and hours growth as well as a significant decline in the correlation. The decline in output volatility can also be traced to less volatile labor input and total factor productivity (TFP) growth and the smaller covariance between them. This relationship suggests that labor market changes such as increased labor market flexibility are an important source of increased output stability. At the industry level, the decline in volatility appears widespread, with about 80 percent of component industries showing smaller contributions to aggregate output volatility after 1984, although most of the aggregate decline reflects smaller covariances between industries. Across industries, there is strong evidence of a decline in the correlation between hours growth and labor productivity growth, suggesting again that the labor market dynamics are part of the decline in U.S. output volatility.
Keywords: O4; E32; 330; productivity; volatility; Volatilität; Produktivität; Wirtschaftswachstum; Arbeitsproduktivität; Dekompositionsverfahren; USA